Study of dynamic analysis of separation devices in gas drying - Gurbanov Abdulaga; Sardarova Ijabika; Damirova Javida (EPJ Web of Conferences)
The article considers the main types of separation equipment used at gas production and gas transportation enterprises. The most common types of separators are given. A new combined design of a gravitational cyclone separator with mesh elements has been developed. A description of the internal structure of the developed separator is given. The characteristics of the initial gas and the gas after separation are given. The effect of gas velocity on the process of separation efficiency is shown. A new direction in the field of gas separation is proposed - the implementation of gas separation in the pipelines themselves. The table shows the results of calculations to determine the rate of gas separation in vertical and horizontal pipelines. The main feature of the principle of operation of the proposed pipe separators, in contrast to the existing gravitational separators operating on the principle of jet breaking, is, on the contrary, in the continuity of the jet of gas and liquid phase.